The relationship between social influence, perceived usefulness, and perceived ease of use on Tokopedia's continued use intention by Gen Z in Surabaya - Povannes, Tyaga Adinata; Immanuel Kairupan, Daniel Joel (Jurnal Mantik, 2025)
A This study aims to examine the influence of Social Influence, Perceived Usefulness, and Perceived Ease of Use on the Continued Use Intention of Generation Z on the Tokopedia platform in Surabaya, using the Technology Acceptance Model (TAM) framework. As a technology-savvy generation, Gen Z often engages with e-commerce platforms such as Tokopedia to shop and fulfill their daily needs. This study applies TAM to explore how Social Influence, together with Perceived Usefulness and Perceived Ease of Use, influence Gen Z's decision to continue using Tokopedia sustainably. Understanding these factors is essential to assess what makes Gen Z decide to continue using Tokopedia in Surabaya. The population in this study is Gen Z (born between 1997-2012) in Surabaya who use the Tokopedia e-commerce platform to carry out online shopping activities. Samples will be taken from 119 respondents based on G*Power calculations. This study uses a quantitative method with data collection through an online questionnaire assisted by an online platform distributed to Gen Z Tokopedia users in Surabaya. Regression analysis was used to evaluate the influence of social influence, Perceived Usefulness, and Perceived Ease of Use on the use of sustainability in Tokopedia